Jin’s 3-Needle Acupuncture Treatment For Gastritis Patients at Griya Sehat Holistic Kalisari - Ridwan, Mohammad; wardoyo, Puspo; Abdullah, Ikhwan; Chandra kurniawan, Leny (Jurnal Indonesia Sosial Sains, 2026)
Gastritis is one of the most common gastrointestinal disorders and is characterized by inflammation of the gastric mucosa that may cause symptoms such as epigastric pain, nausea, bloating, and decreased appetite. The high prevalence of gastric complaints encourages the exploration of complementary therapies that can support conventional treatment. One alternative approach is acupuncture, particularly Jin’s 3 Needle acupuncture, which aims to restore the balance of body energy and improve digestive function. This study aims to describe the implementation and therapeutic outcomes of Jin’s 3 Needle acupuncture in the management of gastritis patients at Griya Sehat Holistic Kalisari, East Jakarta. This research used a qualitative case study approach involving one gastritis patient who underwent six acupuncture therapy sessions over four weeks. Data were collected through observation, interviews, and clinical examinations including tongue and pulse diagnosis based on Traditional Chinese Medicine principles. The therapy applied several acupuncture points such as CV12, PC6, ST36, BL20, BL21, and CV4 with notification techniques and moxibustion. The findings showed gradual improvement in the patient’s symptoms after repeated therapy sessions. Complaints such as heartburn, nausea, bloating, and decreased appetite were reduced and eventually disappeared. Improvements were also observed in tongue appearance, pulse stability, and overall physical condition. These results indicate that Jin’s 3 Needle acupuncture may serve as a complementary therapy for gastritis management. The study implies that acupuncture has potential to support holistic digestive health care and may be further explored in broader clinical research.